The wiji sanglur pancuran mas heirloom keris from the reign of Sunan Gunung Jati Cirebon from the perspective of islamic education philosophy - Hero Prayogo; Mahmutarom; Muh. Syaifudin; Khusnul Khotimah; Ouedraogo Saidoue (At Turots: Jurnal Pendidikan Islam, 2025)
The Wiji Sanglur Pancuran Mas heirloom keris is one of the heirlooms made by Mpu Suro as a symbol of the righteousness of the monotheism of Prince Cakrabuana when he founded and led Caruban Larang. After Prince Cakrabuana was able to prove the power of the Wiji Sanglur Pancuran Mas heirloom keris, in 1479 AD the Wiji Sanglur Pancuran Mas heirloom keris was taken care of and transferred to Sunan Gunung Jati along with the event when he was inaugurated as Susuhunan Carbon Panetep Panatagama Senarat Sunda who resides in the Pakungwati Palace. Sunan Gunung Jati then used the power of the Wiji Sanglur Pancuran Mas heirloom keris for the purposes of preaching and expanding the territory of the Cirebon Sultanate. The purpose of this study is to discover the philosophy behind the need for Sunan Gunung Jati to possess the Wiji Sanglur Pancuran Mas heirloom keris and to discover the philosophical values ​​contained within the Wiji Sanglur Pancuran Mas heirloom keris during the reign of Sunan Gunung Jati. This study uses a qualitative research approach that emphasizes data analysis techniques on formal and argumentative thinking processes, by presenting three trusted sources. The results of the research conducted for nine months include: First, the Wiji Sanglur Pancuran Mas Heirloom Keris is one of the Heirloom Keris with magical powers belonging to Sunan Gunung Jati, which is quite famous and its existence is kept secret, as well as being one of the identities and symbols of the straightness of monotheism of Sunan Gunung Jati when he was a Ulama and Umara in the Cirebon Sultanate; Second, in the Pakem Keris Cirebon, it is explained that the Wiji Sanglur Pancuran Mas Heirloom Keris has a special power: "Wateke maring rejeki, rejeki adoh rejeki parek pada teka, lan tinalukan kaula bala, lan kasambadan panejahe". The recommendations from this research include: First, do not be afraid to admire Keris which is the ancestral heritage of the Indonesian nation; Second, not every Keris is included in the category of Keris Pusaka, so you must be careful when you want to own a Keris, there are many individuals who take advantage of ordinary people by cheating them in many ways, so they sell it at a very high price that is unreasonable; Third, before admiring Keris, prioritize knowing its isoteric and esoteric values; Fourth, do not treat Keris excessively, such as: worshiping, giving offerings, giving sacrifices, and using it as a talisman, this can lead the admirer to acts of polytheism; and Fifth, look for the power of Keris Pusaka that suits the nature or character of the admirer so that it can provide benefits in the future.